2016
DOI: 10.1088/1367-2630/18/1/015008
|View full text |Cite
|
Sign up to set email alerts
|

Tuning thermoelectricity in a Bi2Se3topological insulator via varied film thickness

Abstract: We report thermoelectric transport studies on Bi 2 Se 3 topological insulator thin films with varied thickness grown by molecular beam epitaxy. We find that the Seebeck coefficient and thermoelectric power factor decrease systematically with the reduction of film thickness. These experimental observations can be explained quantitatively by theoretical calculations based on realistic electronic band structure of the Bi 2 Se 3 thin films. This work illustrates the crucial role played by the topological surface s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
44
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 24 publications
6
44
1
Order By: Relevance
“…Moreover, in TI thin films, the relative contribution of surface states to TE transport could be systematically controlled by varying the film thickness. This is demonstrated by a recent experiment on the epitaxial Bi 2 Se 3 TI thin films of varied thicknesses, 47 which shows that the metallic TI surface states become more and more important in thinner films, leading to decreased Seebeck coefficients and power factors. Further enhancement of TE performance can be expected by optimizing E F and introducing disorders or defects into the samples for utilizing the advantage of topological protection.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…Moreover, in TI thin films, the relative contribution of surface states to TE transport could be systematically controlled by varying the film thickness. This is demonstrated by a recent experiment on the epitaxial Bi 2 Se 3 TI thin films of varied thicknesses, 47 which shows that the metallic TI surface states become more and more important in thinner films, leading to decreased Seebeck coefficients and power factors. Further enhancement of TE performance can be expected by optimizing E F and introducing disorders or defects into the samples for utilizing the advantage of topological protection.…”
mentioning
confidence: 84%
“…[37][38][39][40][41][42][43][44] Experimental measurements have also been taken to further investigate the contribution of TI boundary states to thermoelectricity. [45][46][47][48] …”
mentioning
confidence: 99%
“…In addition to the above theoretical progress, our focus issue also features experimental efforts towards the application of TIs as excellent thermoelectric materials. Guo et al [19] showed that TI thin films of Bi 2 Se 3 exhibit decreasing thermoelectric power factor with the reduction of film thickness, and provided a theoretical explanation. These results will shed light on future improvement of thermoelectric performance in TI materials.…”
Section: Topological Insulators With Interactionsmentioning
confidence: 99%
“…TIs are promising for thermoelectrics due to their topological protection, which enables an effective decoupling between electrons and phonons, thus realizing the concept of “electron‐crystal phonon‐glass” . Various novel thermoelectric effects have been demonstrated experimentally in TIs . The thermoelectric efficiency can be evaluated by its figure of merit, italicZT=S2italicGT/()Kel+Kph …”
Section: Potential Applicationsmentioning
confidence: 99%
“…[136][137][138] Various novel thermoelectric effects have been demonstrated experimentally in TIs. [139][140][141] The thermoelectric efficiency can be evaluated by its figure of merit,…”
Section: Thermoelectric Propertiesmentioning
confidence: 99%